Peran Institusi Keagamaan di Maluku dalam Upaya Pemberantasan Korupsi - Henky H Hetharia; Samuel J Mailoa (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
It is an anomaly in the life of the Moluccas’ society that the majority of people who committed the criminal act of corruption are considered as religious people. Besides, they are categorized as diligent, obedient and even fanatic adherent of their religions. The act of corruption is an act not only against the law but also against moral and spiritual values. This article explores the role of religious institutions in spreading moral and spiritual values to prevent Molucca’s people from committing corruption.This article used a qualitative method of both: fieldwork and textual study. For fieldwork, in-depth interview and observation are used to gather data from the prisoners, officers, and workers at the prison (Lembaga Pemasyarakatan Klas IIa) in Ambon. All the data are presented using descriptive analysis. The research shows that the role, function, and accountability of religious institutions in the Moluccas are very weak in preventing and eradicating the criminal act of corruption among the prisoners and the police officers, prosecutors, judges, lawyers, and journalists who played along the criminal act of corruption. Those acts have violated their commitment to stand for justice for all people.